Motor synergies for dampening hand vibration during human walking - Togo, Shunta; Kagawa, Takahiro; Uno, Yoji (Experimental brain research, 2012)
This study investigated the motion required to carry a cup filled with water without spilling it, which is a common human dexterous task. This task requires the individual to dampen hand vibration while walking. We hypothesize that a reduction in hand jerk and a constant cup angle are required to achieve this task. We measured movements while human subjects carried a cup with water (WW task) and with stones (WS task) using a three-dimensional position measurement system and then analyzed joint coordination. We empirically confirmed that the value of hand jerk and the variance in cup angle in the WW task were smaller than those in the WS task. We used uncontrolled manifold (UCM) analysis to quantify joint coordination corresponding to the motor synergy required to reduce the hand jerk and variance of the cup angle. UCM components, which did not affect the hand jerk and cup angle, were larger than orthogonal components, which directly affected the hand jerk and cup angle in the WW task. These results suggest that there is a coordinated control mechanism that reduces hand jerk and maintains a constant cup angle when carrying a cup filled with water without spilling it. In addition, we suggest that humans adopt a flexible and coordinated control strategy of allowing variance independent of the variables that should be controlled to achieve this dexterous task.